2014
DOI: 10.1038/ajg.2014.230
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Predictors of Opioid Use in Inflammatory Bowel Disease: A Population-Based Analysis

Abstract: IBD is an independent risk factor for becoming a heavy opioid user, and heavy opioid use is associated with excess mortality in IBD patients. Clinicians should recognize risk factors for future heavy opioid use among their patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 21 publications
4
87
1
Order By: Relevance
“…This detrimental effect may also be compounded by the reduced levels of endogenous opioids due to stress, given their apparent actions in mitigating opioid tolerance. Together these actions could contribute to heavy opioid use in patients with IBD, a serious outcome given that this is an independent risk factor for mortality 49. Our study identifies a number of potential therapeutic targets, both pharmacological and psychological, that could be examined to help prevent the use of high doses of opioids.…”
Section: Discussionmentioning
confidence: 95%
“…This detrimental effect may also be compounded by the reduced levels of endogenous opioids due to stress, given their apparent actions in mitigating opioid tolerance. Together these actions could contribute to heavy opioid use in patients with IBD, a serious outcome given that this is an independent risk factor for mortality 49. Our study identifies a number of potential therapeutic targets, both pharmacological and psychological, that could be examined to help prevent the use of high doses of opioids.…”
Section: Discussionmentioning
confidence: 95%
“…Randomized trials of antagonists in individuals with inflammatory bowel disease would be another area of interest. Opioids worsen inflammatory bowel disease outcomes, antagonists may spare the use of opioids [189]. There are limited options in treating the irritable bowel syndrome, a disorder associated with visceral hyperalgesia; sigma-1 receptor antagonists may reduce pain in this population.…”
Section: Expert Opinionmentioning
confidence: 98%
“…Sigma-1 receptor antagonists like S1RA reduce visceral hyperalgesia secondary to inflammation [189]. Randomized trials of antagonists in individuals with inflammatory bowel disease would be another area of interest.…”
Section: Expert Opinionmentioning
confidence: 99%
“…National trends have shown that opioid prescription rates for acute and chronic abdominal pain have doubled in recent decades [2426]. The prevalence of opioid use for other GI disorders is also high: recent analyses focused on outpatient opioid use demonstrate that 13 to 43% of patients with inflammatory bowel disease (IBD), chronic pancreatitis and functional GI disorders such as irritable bowel syndrome (IBS) use opioids chronically [2730]. Moreover, a significant number of patients with GI disorders are considered heavy opioid users and may be prescribed large quantities of opioids per prescription [3031].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have called for efforts to closely monitor and curb opioid use among patients with painful GI symptoms and disorders [2830]. Others have suggested that patients with GI symptoms and disorders who require chronic opioids may represent a unique subgroup that should be better understood in an effort to limit opioid therapy that is not essential [33].…”
Section: Introductionmentioning
confidence: 99%